Extending structural health monitoring concepts for bone healing assessment. Issue 4 (22nd January 2016) - Ong, W H; Chiu, W K; Russ, M; Chiu, Z K
Abstract: A series of experimental investigations are performed to show the potential of integrating sensing elements into an external fixation for healing assessment of a fracture femur. This investigation is supported by finite element analyses that highlight the fundamental structural dynamics, which enable a stiffness‐based healing assessment methodology. A saw‐bone femur externally fixated with a Hoffman II will be subjected to an artificial fracture. The healing of the fractured femur is simulated with the curing of epoxy applied to the fractured region. The finite element analyses results will help determine the useful modes for assessing the state of healing of the fracture that can be attributed to the changes in the stiffness of the fixated structure. The findings will be tested against a set of experiments to show how the stiffness‐related quantities can be delineated from the dynamic response. The results reported will show distinct changes to the frequency response functions as the epoxy cures demonstrating the potential of integrating sensors onto an external fixation for healing and fracture union assessment.